Leadership, Communication, and Social Influence : a Theory of Resonance, Activation, and Cultivation. - Ruben, Brent D. (Emerald Points Ser., 2019)
Designed for leadership and communication students, scholars, and practitioners, this book offers a timely exploration into the evolution of leadership, communication, and social influence, and sheds light on how we can all become more responsible leaders, followers, and citizens.